1988
DOI: 10.1677/joe.0.1180389
|View full text |Cite
|
Sign up to set email alerts
|

Day–night rhythm of 5-methoxytryptamine biosynthesis in the pineal gland of the golden hamster (Mesocricetus auratus)

Abstract: 5-Methoxytryptamine is a potent agonist of presynaptic 5-hydroxytryptamine autoreceptors modulating serotonin release in the central nervous system. This methoxyindole can be synthesized in the pineal gland, but its presence in vivo is still controversial, probably because of rapid catabolism by monoamine oxidase. An improved high-pressure liquid chromatography method, with coulometric detection, has been developed for the simultaneous measurement of melatonin, 5-methoxytryptamine, 5-methoxytryptophol and 5-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…The first problem concerns the fast destruction of 5-MT by MAO A. Contrary to melatonin and NAS, the non-acetylated indoleamines in general and 5-MT in particular represent rapidly converted substrates of MAO A [28,46]. Reliable 5-MT measurements in the pineal gland require the presence of MAO inhibitors [28,101].…”
Section: Melatonin Deacetylationmentioning
confidence: 99%
“…The first problem concerns the fast destruction of 5-MT by MAO A. Contrary to melatonin and NAS, the non-acetylated indoleamines in general and 5-MT in particular represent rapidly converted substrates of MAO A [28,46]. Reliable 5-MT measurements in the pineal gland require the presence of MAO inhibitors [28,101].…”
Section: Melatonin Deacetylationmentioning
confidence: 99%
“…Food pellets and tap water were provided ad libitum. 5-methoxytryptamine is only detectable in the pineal gland of golden hamsters after inhibition of monoamine oxidase (Galzin et al, 1988). Consequently, after eight weeks of exposure to these different photoperiods, the animals received at 16.00h on day one an intraperitoneal injection of 100mg/kg pargyline, an inhibitor of monoamine oxidase (MAOI).…”
Section: Animalsmentioning
confidence: 99%
“…A rhythmic synthesis of 5-MT has been shown in the pineal gland of golden hamsters following pargyline administration, higher values being observed during the light period (Galzin et al, 1988). The aim of this study was to determine if the rhythmic secretion of 5-MT depends upon the photoperiodic regime.…”
Section: Introductionmentioning
confidence: 97%
“…Experimentally it has also been observed that 8 weeks of exposure to SP induces a complete gonadal and accessory sex organ atrophy (Masson-P6vet et al, 1987 (Steinlechner et al, 1983 ;Quay, 1963), 5-methoxytryptophol (Beck and P6vet, 1984 ;Skene et al, 1987 ;Mefford et al, 1983), 5-methoxytryptamine (Galzin et al, 1988) and melatonin (for references see Reiter, 1980). The physiological properties of most of these putative pineal hormones are yet poorly defined but on one of them, melatonin, extensive studies have been performed and it is now generally accepted that this hormone is responsible for the mediation of the effects of the pineal.…”
mentioning
confidence: 99%
“…5-methoxytryptamine, one of the 5-methoxyindoles (including melatonin) synthesized in the pineal gland (P6vet, 1983 ;Galzin et al, 1988) is a very potent serotonin (5-HT) autoreceptor agonist inhibiting, in a concentration dependent manner, the electrically evoked release of 3 H-5-HT from superfused rat hypothalamic slices (Galzin and Langer, 1986). This potent effect of 5-methoxytryptamine on the serotoninergic neurotransmission, although not yet fully evaluated, is probably of physiological importance.…”
mentioning
confidence: 99%